Foodborne Bacterial, Viral, and Protozoan Pathogens in Field and Market Strawberries and Environment of Strawberry Farms - Dziedzinska, Radka; Vasickova, Petra; Hrdy, Jakub; Slany, Michal; Babak, Vladimir; Moravkova, Monika (Journal of food science, 2018)
Field-grown strawberries, the environment of strawberry farms and fresh strawberries from marketplaces were examined for bacterial, viral, and protozoan pathogens. The presence of bacteria was determined using culture and real-time PCR (qPCR), presence of protozoa and viruses using qPCR and reverse transcription qPCR, respectively. The highest proportion of positivity was observed for Escherichia coli both in field and purchased strawberries (up to 48.6%). Finding of Cronobacter ranged from 0.6% to 9% both for field and market strawberries. The prevalence of other pathogens (Listeria monocytogenes, Giardia intestinalis, Cryptosporidium sp., and Norovirus) in strawberries was below 4.5%; HAV was not detected at all. Positivity of the environment was determined to be lower than 2.1% for all microorganisms, except for E. coli. The concentration of pathogens in most samples did not exceed 100 CFU/g using culture and 1.8 × 102 GE/g of strawberries or swabbing area 6.1 × 102 GE/mL or swabbing area of environmental samples using qPCR. All studied farms applied preventive measures such as drip irrigation, avoidance of organic fertilizers, and use of mulch foils or gloves for workers to decrease contamination of strawberries. Despite this, certain pathogens were found in fresh strawberries. Even at low concentrations, these pathogens can be a source of infection for consumers. Thus, their presence in strawberries is of particular significance as these are mostly consumed fresh and without any thermal processing. PRACTICAL APPLICATION: Nonlegislatively monitored pathogens of bacterial, viral and parasitic origin were found in strawberries. Monitoring the presence of these pathogens in ready-to-eat food is therefore meaningful and important in terms of food safety, especially in relation to pathogens with low infectious dose (for example, viruses, parasites).
Keywords: Food Microbiology; ready-to-eat; Listeria monocytogenes; jahodník; Escherichia coli; Food Contamination; lidé; berry; Food Safety; počet mikrobiálních kolonií; Norovirus; Cronobacter; Colony Count, Microbial; průmyslově zpracované potraviny; potravinářská mikrobiologie; kontaminace potravin; potravinářská parazitologie; bezpečnost potravin; Food Parasitology; Giardia lamblia; farmy; Farms; Fragaria; environment; Fast Foods; protozoa; Cryptosporidium; Humans